2008
DOI: 10.1007/s00221-008-1430-9
|View full text |Cite
|
Sign up to set email alerts
|

Digit force adjustments during finger addition/removal in multi-digit prehension

Abstract: We explored adjustments in multi-digit coordinated action on a hand-held object with finger addition and removal. The subjects (n= 7) kept a vertically oriented handle at rest using a prismatic grasp as if holding a glass of liquid and then either added one finger to the grasp-the index (I) or little (L) finger-or removed one finger. Three external torques were applied on the apparatus: clockwise, counterclockwise, and no torque. The individual digit forces and moments were recorded with 6-component sensors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
3
19
0
Order By: Relevance
“…Removing the IF and MF induced force changes in the respective remaining finger and synchronized force changes in the RF and LF. The findings reflect previous results on IF and LF removal (Budgeon et al 2008).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Removing the IF and MF induced force changes in the respective remaining finger and synchronized force changes in the RF and LF. The findings reflect previous results on IF and LF removal (Budgeon et al 2008).…”
Section: Discussionsupporting
confidence: 93%
“…In this situation, a significant change and redistribution of the individual finger forces is needed to stabilize the object against slippage and avoid residual torque that may cause tilt of the hand. This new force distribution is achieved synchronously and without delay, suggesting feedforward anticipatory adjustments (Budgeon et al 2008;Santello and Soechting 2000).…”
mentioning
confidence: 95%
“…The present findings are evidence of within-hand motor equivalence that uses different fingers as different degrees of freedom. Of particular relevance to the present study are the observations that subjects can change multidigit force coordination patterns after removing or adding one finger to the grip during object hold with no disruption to the task or its mechanical requirements (Santello and Soechting, 2000;Budgeon et al, 2008). These studies showed that motor output can be reorganized within hand while performing the task with online sensing of the desired manipulation goal.…”
Section: Motor Equivalence In Anticipatory Control Of Manipulationmentioning
confidence: 61%
“…In addition, our patients with CTS showed few alterations of pair correlations with respect to the phase changes. The task-dependent patterns of five-digit grasping have been examined from the perspectives of kinematics and kinetics, and these are coordinated according to the different requirements of the tasks such as the end position or mass of an object [4,10,11,21,30,33]. During lifting and lowering, more emphasis regarding control of the digits' forces should be placed on acceleration and deceleration of objects.…”
Section: Discussionmentioning
confidence: 99%